Experimentation works : the surprising power of business experiments - Thomke, Stefan H., (Harvard Business Review Press, 2020)
"When it comes to innovation, relying on intuition won't cut it anymore. Whether it's improving customer experiences, trying out new business models, or developing new products, even the most experienced managers often get it wrong. This is especially true in the online world, where predicting customer behavior is virtually impossible. Managers can, however, discover whether a new product, service, or business model will fail or succeed--by subjecting it to rigorous experimentation. Think about it. A pharmaceutical company would never introduce a new drug without first conducting a round of experiments based on established scientific protocols. Yet that's essentially what many companies do when they roll out new products and services. As Harvard Business School professor Stefan Thomke shows in this eye-opening and essential book, the "best guess" approach to innovation is changing fast. There are now leading companies that conduct more than ten thousand online controlled experiments annually, engaging millions of users. These organizations have discovered that an "experiment with everything" approach has a big payoff, giving them a considerable competitive advantage. How can you do this at your company? Leaders and managers need to create an "experimentation organization" that masters the science of testing and puts the discipline of experimentation at the center of the innovation process. It used to take companies years to build the infrastructure and develop the expertise to run hundreds of experiments each day. But Thomke shows how, with advances in technology, these capabilities are at the fingertips of almost any business professional. By combining the power of software and the rigor of controlled experiments, today's managers can make better decisions, create better customer experiences, and generate huge financial returns. Filled with engaging and instructive stories of leading experimentation organizations, Experimentation Works will be your guidebook to